2019
DOI: 10.1111/jep.13196
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a patient decision aid on shared decision‐making behaviour in oncology care and pulmonary medicine—A field study based on real‐life observations

Abstract: Objective A patient decision aid (PtDA) is often developed and evaluated to support shared decision making (SDM) and a patient‐centred approach. In this study, a PtDA template was developed to support two different preference sensitive decisions: adjuvant therapy for breast cancer and diagnostic workup for lung cancer. The aim of the study was to explore whether a PtDA improved SDM and supported a patient‐centred approach from an observational point of view. Methods Real‐life observations were conducted using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 23 publications
(50 reference statements)
1
26
0
Order By: Relevance
“…As a result, SDM and PDA uptake may fail to be sustained over time [ 24 ]. Within this context, we studied SDM implementation at Vejle Hospital, Denmark, where, under the leadership of the Center for Shared Decision Making, SDM and PDAs have been implemented with considerable success [ 11 13 ]. The purpose of this qualitative study was to examine practitioners’ experiences of the Center’s efforts to introduce SDM and PDAs into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, SDM and PDA uptake may fail to be sustained over time [ 24 ]. Within this context, we studied SDM implementation at Vejle Hospital, Denmark, where, under the leadership of the Center for Shared Decision Making, SDM and PDAs have been implemented with considerable success [ 11 13 ]. The purpose of this qualitative study was to examine practitioners’ experiences of the Center’s efforts to introduce SDM and PDAs into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…There was a pronounced difference in our results in how clinicians and nurses viewed patient participation; nurses were enthusiastic about SDM due to their first-hand experience seeing the consequences of not taking patients’ wishes into account in treatment decisions, whereas for clinicians this shift happened after working with patients on developing the PDAs and was reinforced through repeated application of SDM principles. Previous findings from the Center have shown that pre-implementation OPTION scores indicated lower levels of SDM [ 11 ]. Communicating this disparity to clinicians may be the first step in shifting attitudes, as clinicians’ perception that SDM improves their practice makes sustained implementation more likely [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients are reluctant to assert their care preferences to clinicians, especially in the face of critical illness. Karina Olling et al report from Denmark their “before and after” study of the effect of a patient decision aid on SDM in this context. Applying a validated tool, the OPTION scale, experienced oncology nurses independently observed decision support to facilitate patient‐centred communication in real life.…”
Section: Shared Decision Makingmentioning
confidence: 99%
“…It includes papers on the nature of reasoning and evidence, the on‐going problems of how to “integrate” different forms of scientific knowledge with each other, and with broader, humanistic understandings of reasoning and judgement, patient and community perspectives . Discussions of the epistemological contribution of patient perspectives to the nature of care, and the crucial and still under‐developed role of phenomenology in medical epistemology, are followed by a broad range of papers focussing on SDM, analysing its proper meaning, its role in policy, methods for realizing it and its limitations in real‐world contexts …”
Section: Introductionmentioning
confidence: 99%